(untitled) (Bangladesh Agronomy Journal, 2023)
Weed management plays an important role in obtaining target yield. A field experiment was carried out at the Agronomy field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh, from July to December 2019 to get the most effective weed control strategy for transplanted Aman rice. The soil of the study field was silty clay loam in nature. The study consisted of two factors i.e., variety (4: Chinigura, BR11(Mukta), BRRI dhan56, and BRRI hybrid dhan6) and herbicide (4) viz., Bispyribac-sodium WP @ 150 g ha-1, Acetochlor 14% + Bensulfuron methyl 4% WP @ 750 g ha-1, Pretilachlor 6% + pyrazosulfuron 0.15% WP @ 9.88 kg ha-1, and weedy check as a control. The experiment was laid out in a split-plot design with three replications. Thirteen weed species were found in the experimental plots, mostly broadleaf and sedge. Monochoria vaginalis was the most dominant weed species. The study noticed that the application of mixed herbicides offered better weed control over single herbicide application. Application of Acetochlor 14% + Bensulfuron methyl 4% WP @ 750 g ha-1 significantly reduced weed density and biomass and was the best way of controlling complex weed flora. The study marked out BR11 (Mukta) as the most potential aman rice variety to produce the highest yields at applying Acetochlor 14% + Bensulfuron methyl 4% WP @ 750 g ha-1. This treatment gave the highest gross return (Tk. 1,46,010), net return (Tk. 88,699), and benefit-cost ratio (2.55). Therefore, the study suggests the application of mixed herbicides and BR11 (Mukta) to get the optimum yield of transplanted Aman rice and maximum economic benefit. Bangladesh Agron. J. 2023, 26(1): 56-74